Water structure, dynamics and ion adsorption at the aqueous {010} brushite surface - Garcia, N.; Raiteri, Paolo; Vlieg, E.; Gale, Julian (M D P I AG, 2018)
Understanding the growth processes of calcium phosphate minerals in aqueous environments has implications for both health and geology. Brushite, in particular, is a component of certain kidney stones and is used as a bone implant coating. Understanding the water–brushite interface at the molecular scale will help inform the control of its growth. Liquid-ordering and the rates of water exchange at the brushite–solution interface have been examined through the use of molecular dynamics simulation and the results compared to surface X-ray diffraction data. This comparison highlights discrepancies between the two sets of results, regardless of whether force field or first principles methods are used in the simulations, or the extent of water coverage. In order to probe other possible reasons for this difference, the free energies for the adsorption of several ions on brushite were computed. Given the exothermic nature found in some cases, it is possible that the discrepancy in the surface electron density may be caused by adsorption of excess ions.